An examination of legal representation on plea bargained sentencing outcomes for criminal defendants - Grube, Johnathan (Kansas State University, 2024)
This dissertation examines the pervasive notion that retained attorneys offer superior legal defense compared to appointed attorneys. Such beliefs hold substantial implications for justice equity, as a defendant's financial resources should not dictate the caliber of their defense or the subsequent sentence they receive. Yet, a dearth of understanding persists regarding the influence of attorney type on sentencing outcomes. This study bridges this gap through a quantitative examination of attorney type and its impact on sentencing. Indigent defendants, unable to bear the financial burden of legal representation, are informed by a judge of the attorney appointed to represent them in criminal proceedings. Judges appoint attorneys because these defendants may lack the means to retain an attorney with a proven track record of trial success, which financially able defendants can readily secure. Consequently, a defendant's limited resources may hinder appointed attorneys from mounting a robust defense, potentially affecting the decision to pursue trial. Therefore, it is crucial to ascertain whether indigent defendants receive equitable representation compared to those capable of retaining their own legal counsel. To address this concern, this dissertation employs bivariate logistic regression models to analyze the impact of defense attorney type on the plea negotiation process, as evidenced by negotiated sentencing outcomes, within Kansas state district courts. Specifically, utilizing sentencing data from the Kansas Sentencing Commission spanning fiscal years 2015 to 2019, this study applied logistic regression analysis to investigate the impact of attorney type across three distinct research questions pertaining to sentence disposition, departure sentences, and the choice between concurrent and consecutive sentences. Notably, all three models yield statistical significance and identified significant variables for each research question. Alongside numerous significant demographic variables, the analysis reveals attorney type as a significant predictor of both sentence disposition and departure sentences. The implications of these findings, alongside theoretical and policy considerations, are thoroughly discussed, aiming to inform future academic and policymaking endeavors.
Keywords: Sentencing; Attorney; Outcome; Indigent; Plea; Defendant